Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. Issue 20 (18th October 2019) - Wang, Zhen-Hui; Xu, Huan-Jun; Zhai, Yang-Yang; Yang, Lan-Ping; Li, Qiang; Huang, Mei; Chen, Xing-Ying; Zhang, Wen-Kui; Meng, Yue-Li; Zhang, Qing-Ling; Niu, Chao; Zhang, Yan-Ru
Abstract: Three new labdane-type diterpenoids, callicapene M3-M5 (1–3 ) were isolated from the Callicarpa macrophylla Vahl. Their structures were identified by spectroscopic method. The isolated compounds were evaluated for inhibitory activity on NO production in LPS-activated RAW 264.7 macrophage cells by using MTT assays. Compounds1 –3 showed potent inhibitory activity, with IC50 value of 48.15, 46.31 and 38.72 μM respectively. GRAPHIC ABSTRACT: